Таълимни глобаллаштириш –цивилизациямиз глобал муаммоларини бартараф этиш воситасидир - Tursunov, Qahor (E-Library Karshi EEI, 2022)
Таълимни глобаллаштириш –цивилизациямиз глобал муаммоларини бартараф этиш воситасидир